Efektivitas Penegakan Hukum melalui Operasi Pekat Semeru dalam Menekan Angka Kriminalitas di Wilayah Kepolisian Resor Tuban - Fani Candra Pramudi Imawan; Agus Ariadi (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
The rising crime rates within the legal jurisdiction of the Tuban Regency Regional Police remain heavily dominated by the prevalence of social vices, including gambling, prostitution, narcotics abuse, and illicit alcohol distribution. The triggers for these persistent offenses are driven by a complex combination of internal and external factors rooted in community dynamics. Employing an empirical juridical research method, this study aims to comprehensively evaluate the effectiveness of law enforcement through the Operasi Pekat Semeru scheme and map out its operational constraints in the field. The research findings indicate that the implementation of this special police operation has contributed positively to maintaining regional stability, public security, and social order. However, law enforcement efforts on the ground still face tangible structural and cultural obstacles. These constraints particularly involve the vast geographical scope of surveillance along the northern coastal highway, limited personnel capacity, and deep-seated socio-economic pressures that trigger criminal recidivism among offenders. Consequently, continuous collaboration among police authorities, local government agencies, and active community elements must be accelerated. Such synergy is highly vital to maximize holistic prevention and eradication strategies against social vices in Tuban Regency.